2021
DOI: 10.1101/2021.05.11.443572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Siglec-1 on dendritic cells mediates SARS-CoV-2 trans-infection of target cells while on macrophages triggers proinflammatory responses

Abstract: COVID-19 pandemic is not yet under control by vaccination, and effective antivirals are critical for preparedness. Here we report that macrophages and dendritic cells, key antigen presenting myeloid cells (APCs), are largely resistant to SARS-CoV-2 infection. APCs effectively captured viruses within cellular compartments that lead to antigen degradation. Macrophages sense SARS-CoV-2 and released higher levels of cytokines, including those related to cytokine storm in severe COVID-19. The sialic acid-binding Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…While other potential receptors have been described for SARS-CoV-2, ACE2 appears to be the primary receptor, and cells that do not express ACE2 are generally resistant to infection [12] . This is consistent with the observation that the virus primarily infects epithelial cells of the lung and gut which express ACE2, although it has also been suggested that SARS-CoV-2 can infect other cell types within the body, including cardiomyocytes, neurons, endothelial cells, and some leukocytes [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…While other potential receptors have been described for SARS-CoV-2, ACE2 appears to be the primary receptor, and cells that do not express ACE2 are generally resistant to infection [12] . This is consistent with the observation that the virus primarily infects epithelial cells of the lung and gut which express ACE2, although it has also been suggested that SARS-CoV-2 can infect other cell types within the body, including cardiomyocytes, neurons, endothelial cells, and some leukocytes [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionsupporting
confidence: 87%
“…For instance, sialylated secreted glycoproteins from SARS-CoV-2 can bind to and activate host Siglecs thus downregulating the antiviral response [104] . Furthermore, SARS-CoV-2 viral spike proteins contain α2,6 and α2,3 linked sialic acids that enable their interaction with Siglec-1, Siglec-3, Siglec-9, and Siglec-10, facilitating their entry into host immune cells [19] , [105] , a phenomenon which can be blocked with an anti-Siglec-1 monoclonal antibody [19] ( Figure. 1 A ).…”
Section: Siglec Signaling In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The biologic biosafety committee of Germans Trias i Pujol Research Institute (IGTP) approved the execution of SARS-CoV-2 experiments at the BSL3 laboratory of the Centre for Bioimaging and Comparative Medicine (CSB-20-015-M8; CMCiB, Badalona, Spain). The SARS-CoV-2 variants used in this study were isolated from nasopharyngeal swabs of hospitalized patients in Spain as described elsewhere ( Perez-Zsolt et al, 2021 ; Rodon et al, 2021 ). Briefly, viruses were propagated in Vero E6 cells (CRL-1586; ATCC, Virginia, VA, United States) for two passages and recovered by supernatant collection.…”
Section: Methodsmentioning
confidence: 99%
“…The biologic biosafety committee of Germans Trias i Pujol Research Institute (IGTP) approved the execution of SARS-CoV-2 experiments at the BSL3 laboratory of the Centre for Bioimaging and Comparative Medicine (CMCiB, Badalona, Spain). The SARS-CoV-2 variants used in this study were isolated from nasopharyngeal swabs of hospitalised patients in Spain as described elsewhere (Perez-Zsolt et al, 2021; Rodon et al, 2021). Briefly, viruses were propagated in VeroE6 cells (CRL-1586; ATCC, Virginia, VA, USA) for two passages and recovered by supernatant collection.…”
Section: Methodsmentioning
confidence: 99%